Trabalho, valor e tecnologia na indústria 4.0: como as revoluções industriais aprofundam a produção de mais-valor relativo - Souza, Willams Gomes de (2024)
The aim of this paper is to analyze, from the perspective of the Marxian critique of value, some aspects of the transformations in the degree of productivity of the workforce, resulting from the technological development of productive work, with emphasis on the question of relative surplus value in the fourth industrial revolution. From the perspective of the production of surplus value as the substance of the capitalist accumulation process, it aims, in the wake of the concept of the collective worker (Gesamtarbeiter), to analyze some of the effects of the transformations brought about by the industrial revolutions, especially the so-called Industry 4.0. The main reading key adopted is the following: in the process of real subsumption of labor to capital in the fourth industrial revolution, not only does living labor (workforce) replace dead labor (machines), but also, and above all, the fact that dead labor “comes to life” over living labor stands out, so that dead labor begins to act as if it were an autonomous subject in the production process. The methodology used was bibliographical and documentary research guided by the ontological-dialectical perspective.